A numerical study of the thermal transient in high-pressure diesel injection. (January 2017) - Arienti, Marco; Sussman, Mark
Highlights: High-fidelity simulations of high-pressure Diesel injection are carried out showing the effect of internal injector flow dynamics on spray formation. The test cases demonstrate the feasibility of fully compressible two-phase simulations with time-resolved interface capturing. The effects of injector flow dynamics on the exit fuel temperature are illustrated using a complete equation of state for n-dodecane. Differences in spray characteristics resulting from adiabatic and isothermal wall boundary conditions are identified and discussed. Abstract: A study of n-dodecane spray atomization, following the prescribed unseating of the injector's needle tip, is presented for a high-pressure, non-cavitating Bosch Diesel injector ("Spray A", in the Engine Combustion Network denomination). In the simulations discussed here, the internal and external multiphase flows are seamlessly calculated across the injection orifice using an interface-capturing approach for the liquid fuel surface together with an embedded boundary formulation for the injector's walls. Another novelty is the capability to model the compressibility of the liquid and the gas phase while maintaining a sharp interface between the two. This setting makes it possible to directly relate time-dependent spray characteristics to the moving internal geometry of the injector and to the exit thermodynamic state of the fuel. Using the Tait's equation of state calibrated for n-dodecane, we examine the differences in jet atomization between adiabatic and isothermal wall conditions.